Mobile cloud computing prototype for emergency health care model - Nirabi, Ali (Kulliyyah of Engineering, International Islamic University Malaysia, 2019)
In emergency healthcare processes, the time is very important factor, the seconds and minutes can be the difference between life and death. Implementing the latest mobility technologies can make the emergency healthcare services more rapid and reliable. This study focuses on building a mobile cloud computing for emergency health care prototype of MCCEH to overcome many of current weakness in healthcare emergency systems. The main aim of this research study is to incorporate health care emergency services and reduce the emergency's response time that may help to safe the patient's life, at beginning prototype of MCCEH will detect patient's location and will find the nearest emergency medical centers or specialists by specific category based on patient case which center able to cover patient's insurance. After the booking is done, the patient's information and location will be shared to ambulance/specialist and they can navigate the address using GPS service to get shortest road and they can get the patient's record based on shared information. In the meantime to arrive the location, prototype of MCCEH will provide feature to make (video call, share pictures and send messages) between ambulance and patient to share more clear pictures in the scene which allow the doctor to give an advice or initial diagnose. Prototype of MCCEH services are hosted on cloud computing server to provide quick, reliable and quick response and the prototype have been tested and evaluated for 12 thousand users requests with response time 1305ms, the limitation of study is the cost proposing the system has been published in Malaysia or other big countries, having millions of requests eg. 100,000, 3000,000 the cloud computing will keep increasing the resources which will cause very big amount of costs.